Renal lymphangiectasia presenting with hypertension and polycythemia - Blanc, Mathieu; Schmutz, Gérard; Belzile, François; Sabbagh, Robert (Canadian Urological Association Journal, 2014)
We report a very rare case of renal lymphangiectasia, an accumulation of lymph in the renal lymphatic system secondary to obstruction. Our patient presented to his family doctor for an annual check-up which resulted with high blood pressure and polycythemia. An ultrasound was performed and revealed a large right perirenal collection. A year later, a controlled abdominal computed tomography scan showed a progression and compression of perirenal collection on the right kidney, as well as apparition of a left perirenal collection. Percutaneous drainage of both collections was unsuccessful. Laparoscopy-guided marsupialisation was performed and successful. Blood pressure lowered to normal range without medication. The patient’s hemoglobin level decreased within normal range after 3 additional phlebotomies postoperatively.